Utilizing Requirement Testing Methods on Web-Based Swab Data Information System - Defni, -; Johan, -; Putra, Andani Eka; Nova, Fitri; Andriani, Wiwik (International Journal of Advanced Science Computing and Engineering, 2022)
The spread of the virus caused by SARS-CoV-2 has been designated as an extraordinary event so that the government to speed up the collection and management of this disease then appoints several hospitals that serve as referral hospitals for people who want to check themselves. One of the hospitals used as a reference by the government in West Sumatra is Andalas University hospital. In just one day, the hospital received thousands of samples for examination. The number of samples to be examined and the limited number of administrations that conduct data collection results in the length of the sample collection process. This article aims to design and implement an information system in the data collection of Swab Covid-19 using waterfall model system development methods. The requirement testing model is used for testing a web-based Covid 19 swab data information system whether it is in accordance with system users' needs analysis and design.